Responsiveness of quantitative cartilage measures over one year in knee osteoarthritis: Comparison of radiography and MRI assessments. Issue 1 (11th April 2013) - Cromer, Megan S.; Bourne, Roger M.; Fransen, Marlene; Fulton, Roger; Wang, Shih‐Chang
<x xml:space="preserve">Abstract</x> Purpose To directly compare the responsiveness of quantitative imaging measures of disease progression in knee osteoarthritis (OA). In the medial compartment of the knee comparison was made between: 1) radiographic joint space narrowing (JSN); 2) global quantitative magnetic resonance imaging (qMRI) of cartilage volume; 3) regional qMRI of cartilage thickness; and 4) regional analysis using an ordered value (OV) methodology. Materials and Methods 3T MRI and weight‐bearing radiography of the knees were performed at baseline and 1‐year timepoints in 23 subjects (mean age 63 years) with symptomatic knee OA. Standardized response means (SRM) were calculated for each measure. Statistical analysis to determine significance of change between timepoints was performed with a two‐tailed Student's t‐test (JSN, global, regional analysis) and nonparametric Mann‐Whitney test (ordered values). Results At 1 year, global cartilage volume losses of 2.3% (SRM −0.44) in the medial tibia and 6.9% in the medial femur (SRM −0.74) were recorded. SRM for JSN was −0.46. Regional analysis revealed largest reductions in cartilage thickness in the external (SRM −0.84) weight‐bearing subregion of the medial femur and in the posterior subregion of the medial tibia (SRM −0.79). OV analysis in the medial compartment revealed areas of cartilage thinning (four ranked OV) and cartilage thickening (two ranked OV). Conclusion The MRI OV approach proved to be a superior analysis tool for detecting changes in cartilage morphology over a 1‐year period. Radiographically defined JSN was found to be the least responsive measurement method of knee OA disease progression. J. Magn. Reson. Imaging 2014;39:103–109. © 2013 Wiley Periodicals, Inc.